Characterization of people living with HIV in a Montreal-based tertiary care center with COVID-19 during the first wave of the pandemic. Issue 5 (4th May 2022) - Fehr, Derek; Lebouché, Bertrand; Ruppenthal, Luciana; Brownc, Melodie; Obasc, Nancy; Bourbonnière, Emilie; Girouard, Josee; Massicotte, Angie; Jenabian, Mohammad-Ali; Almomen, Abdul-Aziz; Frenette, Charles; de Pokomandy, Alexandra; et al.
ABSTRACT: People living with HIV (PLWH) often have worse health outcomes compared to HIV-uninfected individuals. We characterized PLWH followed at a tertiary care clinic in Montreal who acquired COVID-19 and described their outcomes during the first wave of the pandemic. A retrospective chart review was performed for PLWH followed at the Chronic Viral Illness Service with a positive COVID-19 nasopharyngeal PCR or symptoms suggestive of COVID-19 between 1 March and 15 June 2020. Data on demographics, socioeconomic status, co-morbidities and severity of COVID-19 and outcomes were extracted. Of 1702 individuals, 32 (1.9%) had a positive COVID-19 test ( n = 24) or symptoms suspicious for COVID-19 ( n = 3). Median age was 52 years [IQR 40, 62]. Nearly all (97%) earned 34, 999 Canadian dollars or less. Eleven (34%) individuals worked in long-term care (LTC) homes while 5 (6%) lived in LTC homes. Median CD4 count was 566 cells/mm 3 [347, 726] and six had detectable plasma HIV viral loads. Median duration of HIV was 17 years [7, 22] and 30 individuals had been prescribed antiretroviral therapy. Five persons were asymptomatic. Of symptomatic persons, 21 (12%), 1 (4%) and 3 (12%) individuals had mild, moderate and severe disease, respectively. Three individuals died with COVID-19. In one case, the cause of death was due to COVID-19, whereas in the other two cases, the individuals died with positive COVID-19 test results but the immediate cause of death is unclear. PLWH who tested positive for COVID-19 had low socioeconomic status and had employment or living conditions that put them at high risk. PLWH may be disproportionately impacted by the social determinants of health which predispose them to COVID-19.